Long-term impact of the coach-athlete relationship on development, health, and wellbeing: stories from a figure skater - Kuhlin, F.; Barker-Ruchti, N.; Stewart, C. (Sports Coaching Review, 2020)
Coaches have been shown to detriment athletes` health, well-being and development. Knowledge of this long-term effect and what it means for athletes to live with such stories is under-explored. Using self-narrative, we examine the long-lasting impact of the coach-athlete relationship in the stories of a former figure skater, Fanny. Guided by Arthur Frank`s dialogical analysis, we present creative non-fictional stories to show how Fanny made sense of her figure skating experiences, which were framed by a sport investment narrative and a career-wrecking injury that terminated her dream of becoming a professional figure skater. We suggest that if handled as an act of self-care, storytelling can re-configure the dominant coach-athlete relationship and sport investment narrative and help athletes to understand and reconstruct their stories. Finally, we reflect upon the impact of Fanny`s story on her advisers and consider the pedagogical implications of such narrative work in sport coaching and sport education.